The Impact of the Use of Social Media Sites on the Cognitive Empowerment of Postgraduate Students (The International Journal of Educational Sciences and Arts, 2023)
The current study aims to recognize the impact of the use of social media sites on cognitive empowerment among postgraduate students. To achieve the study's objectives, my measure of social media sites and cognitive empowerment was developed, and their psychometric characteristics were verified. The study sample was selected from graduate students from Saudi universities in the second semester of 2022-2023. (256) Students, relying on the analytical forecasting curriculum in this study, the results of study found that social media sites affect knowledge empowerment by (5%) and that male students are better than female students in cognitive empowerment, While there were no differences between students and students on social media sites and there were no differences in social networking and cognitive empowerment according to the type of kidney and marital status, Based on the study's findings, some recommendations were made, including the need to develop the positive impact of social media sites as they play a role in their knowledge empowerment.
Keywords: Social media sites; Cognitive empowerment; Postgraduate students